Perceptions of Vegetable Farmers in Wajo District Towards Marketplace Implementation - Musdalipah Musdalipah; Muliati Muliati (International Journal of Artificial Intelligence Research, 2022)
This research was conducted in Wajo Regency. The research was conducted for 1 (one) month, from April to June 2022. The objective to be achieved in this study is to determine the form of vegetable marketing that has been applied in Wajo Regency, This research uses descriptive qualitative research. The type of research used in this research is descriptive research with a qualitative approach. namely through interviews to respondents in a structured manner using a questionnaire or list of questions that have been prepared in advance and through observation, namely data collection using direct observation of the use of digitalization through the marketplace at the research location. The results of descriptive analysis show that the perception of vegetable farmers towards the application of the marketplace in Gilireng and Belawa Districts, Wajo Regency is in the